2020
DOI: 10.1007/s12671-020-01462-y
|View full text |Cite
|
Sign up to set email alerts
|

An Effectiveness Study of a Digital Mindfulness-Based Program for Upper Secondary Education Students

Abstract: Objectives Mindfulness-based programs/interventions (MBPs) are emerging as treatments for anxiety and stress for adults and adolescents. MBPs can also be helpful as universal interventions for healthy subjects. Few studies have looked at how beneficial MBP effects transfer to digital MBPs. Methods The study was a randomized controlled trial with 1349 participants aged mostly 16–19. We compared a digital MBP vs. a waitlist condition. Online questionnaire data were collected pre-program, post-program, and at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The most frequently assessed mental health outcomes were depression or depressive symptoms ( n = 38; 84%), anxiety-related symptoms ( n = 33; 73%), psychological stress level (n = 14, 40%). Several studies also investigated mental health outcomes relating to mental health wellbeing, 13,20,25,32,44,45 quality of life, 32,36,37,46 life satisfaction, 21,44 psychological distress, 16,25,37,45 insomnia 47 and sleep quality. 43…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most frequently assessed mental health outcomes were depression or depressive symptoms ( n = 38; 84%), anxiety-related symptoms ( n = 33; 73%), psychological stress level (n = 14, 40%). Several studies also investigated mental health outcomes relating to mental health wellbeing, 13,20,25,32,44,45 quality of life, 32,36,37,46 life satisfaction, 21,44 psychological distress, 16,25,37,45 insomnia 47 and sleep quality. 43…”
Section: Resultsmentioning
confidence: 99%
“…Web-based self-help platforms were the most frequently used online format ( n = 35). 14,20,2527,29,30,33,34,36,37,39,40,4244,4655 A total of 24 studies were effective in managing mental health issues whilst other 11 were found to be not effective.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the sex balance in the sample was lopsided with more than five times more females than males. This is a common finding in volunteerbased mindfulness studies, as females appear to volunteer more often than males to mindfulness studies (e.g., Lahtinen & Salmivalli, 2020). Using a sample of volunteers is also a limitation, as there may be a reason to self-select, which leads to bias.…”
Section: Limitations Strengths and Future Directionsmentioning
confidence: 99%